In vitro production of immunosuppressive factors by murine sarcoma virus-transformed mouse fibroblasts. - Mizel, S B (1980)
Murine sarcoma virus-transformed mouse fibroblasts produce potent immunosuppressive factors (ISF) in vitro. The partially purified ISF inhibited thymocyte proliferation induced by concanavalin A or phytohemagglutinin plus lymphocyte activating factor (Interleukin 1), lipopolysaccharide-induced spleen cell proliferation, the in vitro splenic anti-sheep erythrocyte plaque-forming cell response, and the generation of alloantigen-specific cytotoxic T cells. The effect of ISF on thymocyte proliferation was not readily reversible and required only a 4-hr exposure of the thymocytes to ISF to inhibit cell proliferation. Although ISF shares several biochemical properties with a murine sarcoma virus-transformed cell-derived sarcoma growth factor (e.g., acetic acid solubility and sensitivity to dithiothreitol), the two factors could be resolved by gel filtration on Bio-Gel P-60. Two peaks of ISF activity were found with apparent molecular weights of 12,000 and 8000. The results described here support the hypothesis that at least some of the ISF obtained from the serum of tumor-bearing hosts may be released by the tumor cells themselves. In view of the potent in vitro activity of the murine sarcoma virus-transformed fibroblast-derived ISF, it is quite possible that ISF-like molecules may play a role in subverting in vivo tumor rejection processes involving the immune system.